The Effect of Rivet Arrangement on the Strengths of Lap Joints and Lap Joint Design Methods - Kerong Ren; Haobing Han; Wentao Xu; Hua Qing (Applied Sciences, 2023)
To address the impact of rivet arrangement on the strengths of riveted lap joints, the failure modes and failure mechanisms of riveted lap joints were first studied using finite element analysis software. Next, the effects of the number of rivets, rivet rows, rivet arrangement, and row spacing on the lap joint strength were studied using the peak load as the evaluation index. Then, we proposed the concept of line load density to solve the problem that a varying rivet spacing and rivet edge distance will change the width of the sheet and thus the maximum load capacity, which is used as an index to study the effect of rivet spacing and rivet edge distance on the lap strength. Finally, a spring–mass model was developed to study the forces present in multi-row riveting. The model could accurately calculate the force–displacement curves during tensioning. The results show that when multiple rivet rows are used, higher stress concentrations cause the plate to first fracture at an outer rivet row with more rivets; therefore, the rivets should be arranged such that there are more rivets in the middle and fewer rivets on both sides. When the total rivet strength is greater than the remaining strength of the plate, the numbers of rivets and rivet rows have limited effects on the lap joint strength; however, this primarily affects the damaged form of the lap joint member. When the rivet spacing is less than 5d, the lap strength increases with increases in the rivet spacing, and when the rivet spacing is greater than 5d, the lap strength does not change significantly with increases in the rivet spacing. When the rivet edge distance is less than 3d, the lap joint strength increases with increases in the rivet edge distance, and when the rivet edge distance is greater than 3d, it has a limited effect on the lap joint strength. The rivet row spacing has no significant effect on the lap joint strength. The results of this study are valuable for improving the strengths of riveted structures in aircraft.